Substituent Effect: Synthesis of Three TNP‐Detecting Fluorescent Probes Based on Triazolothiadiazole‐Quinazolinone. Issue 26 (8th July 2022) - Zhang, Chenglu; Wang, Yiming; Jiang, Yanhua; Zhang, Yining; Xie, Yanxuan; Gong, Rongqing; Hao, Qiang
Abstract: Three novel fluorescent probes (QZLSZ‐1 ∼QZLSZ‐3 ) were designed and synthesized based on quinazolinone for comparing the representative substituent effects on QZLSZ fluorescence detection of 2, 4, 6‐trinitrophenol (TNP). The results show that the probes all exhibit high selectivity and good photo‐stability in wide pH rang and high quenching efficiency, indicating the rational structural design. Compared the substituent effects on the fluorescent properties of QZLSZ, it is found that electron ‐ donating group in QZLSZ ‐1 is more favorable than the electron‐withdrawing group in QZLSZ ‐3 . The probe QZLSZ ‐1 has the highest fluorescence quantum yield (0.5407) and the biggest Storks shift (191 nm). Furthermore, it has the lowest detection limit (0.16 μM), the optimal sensitivity (1.3 × 10 5 M −1 ), the largest detection range (10∼50 μM) and the rapidest response time (60 s) for the fluorescence recognition of TNP. The theoretical calculation results using Density functional theory (DFT) are highly consistent with that of the experiments. Particularly, QZLSZ‐1 has the best practical application value for qualitative and quantitative fluorescence detection of TNP in actual water samples. Abstract : Three novel fluorescent probes (QZLSZ‐1∼QZLSZ‐3 ) were designed and synthesized based on quinazolinone for comparing the representative substituent effects on QZLSZ fluorescence detection of 2, 4, 6‐trinitrophenol (TNP). Comparing the substituent effects, the electron donating group (methoxy group) produce the best effect among them. Thus QZLSZ‐1 has high quantum yield and large Stokes shift, shows rapid response, low LOD, high selectivity and great sensitivity at wide pH range to TNP